ASSOCIATION REPORTS. - Littleton, A. C. (The Accounting Review, 1945)
Abstract Representative programs from sixty colleges and analyses of them have appeared in four earlier issues of periodical The Accounting Review. In the section published in October the educational pattern was presented in a number of frequency tables showing the distribution of courses among the several departments of instruction. It is now proposed to show the pattern as it is reflected in the titles of the courses taken by this group of sixty students. The commerce courses will be examined first. These include accountancy, economics, business administration and business law. The data about courses in non-commerce subjects will follow. The content of a specific course is not too well foreshadowed by the title of the course. And this limitation would still apply in some degree if the text book used were also named. Although course names are not standardized and sometimes seem unnecessarily vague, they nevertheless can furnish some useful clues to the educational pattern followed by the students concerned. For students who major in accountancy, the courses in that department naturally bulk large in most programs. At the top of the list are the courses called by various titles that indicate they are introductory and intermediate.